ENGLISH PHONOLOGICAL AWARENESS A Descriptive Study of First Grade Students at an Elementary School in Northern Bandung - Nilasar Karinda Putri (Passage, 2017)
This study aims to investigate first grade students’ awareness in English phonology and the factors influencing English phonological awareness. This study employs a mixed method that uses quantitative and qualitative data such as an assessment test, the questionnaire, and the interview as the data collection. The result of the findings indicates that students’ performance on English phonological awareness emerges from the sound units in the level of syllable, onset-rime, and phoneme. Factors, for instance the chronological order of language acquisition and language proficiency, have a positive effect towards the performance of students’ English phonological awareness. The students may commit a transfer, between the target language and another language previously acquired, that can potentially influence the performance in language development. The reason is because the performance on English phonological awareness is as same as in Indonesian phonological awareness.Keywords: phonological awareness, factors influencing English phonological awareness, first grade students, English as a foreign language